2014
DOI: 10.1039/c4ay00119b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of organic compounds and boron clusters with new silica matrices containing the phosphatidylcholine headgroup

Abstract: New matrices were prepared in order to understand the interaction of dodecaborate clusters with liposome surfaces. Interaction is not only through ionic forces, although the clusters are anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It is interpreted by the fact that dodecaborate act as hydrophilic but superchaotropic anion in water solution. 30,[44][45][46][47] It means that water is less structured and more "lipophilic" around such anions as compared to bulk water. Association of chaotropes with cyclodextrins is explained not in terms of hydrophobic action but as so-called chaotropic effect because it is enthalpy driven.…”
Section: Introductionmentioning
confidence: 98%
“…It is interpreted by the fact that dodecaborate act as hydrophilic but superchaotropic anion in water solution. 30,[44][45][46][47] It means that water is less structured and more "lipophilic" around such anions as compared to bulk water. Association of chaotropes with cyclodextrins is explained not in terms of hydrophobic action but as so-called chaotropic effect because it is enthalpy driven.…”
Section: Introductionmentioning
confidence: 98%
“…Boron clusters have found numerous applications. The discovery of boron clusters in the 1960s opened access to a new form of boron carrier for neutron capture therapy (NCT) of cancer . Dodecaborate anions, with their chaotropic nature, interact with proteins, carbohydrates, and membranes. Recently, we have reported the supramolecular host–guest complexation of dodecaborate clusters of the type B 12 X 12 2– and B 12 X 11 Y 2– (X = H, Cl, Br, I and Y = OH, SH, NR 3 + ) with CDs . Strong inclusion complexes were formed, particularly with γ-CD, reaching record micromolar affinities in aqueous solution …”
mentioning
confidence: 99%
“…Previously, we investigated the interaction of these and other boron clusters with immobilized egg phosphatidylcholine liposomes 20. We found that especially BBr and BI interacted so strongly with the liposomes that they could not be eluted, whereas BCl was not retained very strongly.…”
Section: Discussionmentioning
confidence: 94%